2015
DOI: 10.1080/17441692.2015.1014825
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and knowledge of voluntary medical male circumcision for HIV prevention in traditionally non-circumcising communities in South Africa

Abstract: Voluntary medical male circumcision (VMMC) has been recommended for the prevention of HIV transmission, particularly in sub-Saharan Africa. Uptake of the campaign has been relatively poor, particularly in traditionally non-circumcising regions. This study evaluates the knowledge, attitudes and practices of medical male circumcision (MC) of 104 community members exposed to promotional campaigns for VMMC for five years. Results show that 93% of participants have heard of circumcision and 72% have heard of some h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
6
5
Order By: Relevance
“…A study conducted done in South Africa showed that 75.5% of participants understood the partial protection offered by VMMC a percentage slightly lower as compared to this study [32] while another study conducted in Botswana, Namibia and Swaziland showed that 9.0-15.0% of the participants believe that circumcised men are fully protected against HIV compared to 12.7% from this current study [33]. Almost all of the participants reported the need to continue using condoms post VMMC and that one can still transmit the virus despite having undergone VMMC.…”
Section: Discussioncontrasting
confidence: 78%
“…A study conducted done in South Africa showed that 75.5% of participants understood the partial protection offered by VMMC a percentage slightly lower as compared to this study [32] while another study conducted in Botswana, Namibia and Swaziland showed that 9.0-15.0% of the participants believe that circumcised men are fully protected against HIV compared to 12.7% from this current study [33]. Almost all of the participants reported the need to continue using condoms post VMMC and that one can still transmit the virus despite having undergone VMMC.…”
Section: Discussioncontrasting
confidence: 78%
“…A study done in South Africa showed that 75.5% of clients understood the partial protection offered by VMMC a percentage slightly lower as compared to this study [30]. A similar study conducted in Botswana, Namibia and Swaziland showed that between 9 and 15% of the clients believe that circumcised men are fully protected against HIV compared to 2.5% from this current study [31].…”
Section: Discussioncontrasting
confidence: 65%
“…(Table 7) On transactional sex, age, marital status, location and occupation were significantly associated with engaging in transaction sex. The odds of being involved in transactional sex among those aged [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] was 81% less compared to those aged 18-29 (OR 0.19, 95% CI 0.09, 0.37 p <0.0001). The odds of being involved in transaction sex among the married ones was 88% less compared to those that were single (OR 0.12, 95% CI 0.07, 0.22 p <0.0001).…”
Section: Univariate and Multivariate Analysis On Sexual Practicesmentioning
confidence: 99%
“…These results are similar to those of studies done in non-circumcising communities in South Africa, where was found that 93.3% had heard about circumcision, although only 23.3% of respondents were circumcised. [26] The awareness of MC in this study may be attributed to the announcement of the South Africa, Kenya and Uganda RCTs on the association between MC and HIV infection [6,7] and the announcement by the Namibian government to embark on the introduction of safe MC to the public in 2008. The association between MC and health benefits (reduced risk of HIV and STIs, penile hygiene enhancement) was prevalent in this study.…”
Section: Discussionmentioning
confidence: 99%